PENINGKATAN MUTU PENDIDIKAN DI PERGURUAN TINGGI: SEBAGAI ALTERNATIF PENANGGULANGAN PENGANGGURAN TERDIDIK - Suryanti, Eny Wahyu (FKIP Universitas Wisnuwardhana, 2019)
Educated unemployment has indeed had a negative impact on education, both in social stability and society. Improving the quality of tertiary education is very necessary in managing and developing tertiary institutions with modern management principles oriented to quality. In realizing the improvement of the quality of education, there are several aspects that must be considered, namely 1) the education system must be routinely evaluated with reference to the development of science, technology and art and global developments in the world community, 2) improving the quality of students including; setting quality standards for student selection, learning discipline, character building, and skills development, 3) improving the quality of lecturers in recruitment, career path, performance, development of science, teaching, research, service, and welfare, 4) Curriculum development based on market needs work, and 5) developing infrastructure to support the education and teaching process. Keywords: quality of education, higher education, educated unemployment